Neuroendocrine neoplasms of the digestive tract: retrospective classification according to the 2019 WHO grading system, and evaluation of the immunohistochemical marker INSM1 - Aldera, Alessandro Pietro (Department of Pathology, 2020)
Neuroendocrine Neoplasms (NENs) of the Gastrointestinal Tract (GIT) are a heterogeneous group of tumours with varied biologic potential and clinical outcomes. They are classified as well differentiated neuroendocrine tumours (WD NET) or poorly differentiated neuroendocrine carcinomas (PD NECs) based on morphology. WD NETs are further subtyped (grade 1, 2 or 3) by evaluating the mitotic rate and Ki-67 proliferative index. The most recent grading system was published in 2019 by the World Health Organisation (WHO). Insulinoma-associated protein 1 (INSM1) is a transcription factor that is expressed in neuroendocrine cells, and recent studies have shown that it is a sensitive and specific marker for neuroendocrine differentiation. The aims of this study were to grade NENs of the GIT according to the 2019 WHO grading system, and to evaluate the expression of INSM1 in order to assess its sensitivity and specificity as a marker of neuroendocrine differentiation compared to chromogranin A (CgA) and synaptophysin (SYN). Sixty-nine GIT NENs diagnosed between 2003 and 2017 at Groote Schuur Hospital were included in this study. The mitotic rate and Ki-67 proliferation index were evaluated for each case. We identified 38 grade 1 NETs, 16 grade 2 NETs, 1 grade 3 NET, 13 small cell type NECs and 1 large cell type NEC. INSM1 immunohistochemical staining was performed on all cases. To assess specificity, we evaluated the expression of INSM1 in other GIT primary tumours (adenocarcinoma, gastrointestinal stromal tumour, lymphoma, leiomyoma and Kaposi sarcoma). Eighty percent of our NEN cases stained with INSM1. We found the sensitivity of INSM1 to be higher than CgA (68%), but lower than SYN (87%) and the combined use of CgA-SYN (94%) when considering all NENs. When evaluating only the PD NEC cases, INSM1 had a higher sensitivity than CgA (50%) and SYN (64%), and an equal sensitivity to the combined use of CgA-SYN (79%). We conclude that the high sensitivity and specificity of INSM1 make it a valuable standalone marker for assessing neuroendocrine differentiation. The nuclear reactivity and high sensitivity of INSM1 make it the preferred neuroendocrine marker for PD NEC.